Income Inequality Trends in the 1980 s: A Five Country Comparison - Johan Fritzell (Luxembourg Income Study (LIS), 1992)
This paper examines the increase in inequality of income distribution that developed in the 1980's in five western societies. Three possible causal factors are examined, with some surprising result. Cross national variations in level and changes of inequality are also examined.
Keywords: 330